The Relationship Of KB Counseling With The Participation Of First Age Couples ( PUS ) Become A FP Acceptance In Gasaribu Village, Laguboti District Year 2021 - Munarni Simatupang (Science Midwifery, 2021)
From the results of the initial survey conducted by the author of 12 PUS in Gasaribu Village, the authors found 6 of them said that they had heard about family planning contraceptives but were not interested in becoming family planning acceptors because of wrong understanding or myths about contraception, one of which was the side effect of contraception. use of contraceptive methods and feelings of embarrassment because the contraceptive device is placed on their genitals. And 6 other people said they knew about the contraceptive method but did not use it because they wanted to have more children. Univariate analysis is an analysis that focuses on the depiction or descriptive of the data obtained. Describe the frequency distribution of each of the independent variables and the dependent variable. Bivariate analysis to see the relationship between family planning knowledge of reproductive age couples in using contraceptives. The data collected were analyzed using the chi square statistical test. Most of the respondents did not participate in the family planning program as many as 54 respondents (72.97%), while PUS who participated in the family planning program were as many as 20 respondents (27.03%). Based on the results of the study, it can be concluded that the majority of respondents' knowledge (PUS) about family planning in Gasaribu Village, Laguboti District, Toba Regency, has good knowledge, as many as 35 respondents (71.00%). 20 respondents (67.3%) did not participate in the family planning program, while 54 respondents (3 2, 7%) did not participate in the family planning program. The highest percentage of family planning participation based on cross tabulation of respondents with less knowledge was 8 respondents (34.7%), while the highest percentage did not participate in family planning programs with good knowledge as many as 27 respondents (77.2%). There is no significant relationship between the level of knowledge about family planning and participation in family planning in PUS in Gasaribu Village, Laguboti District, Toba Regency in 2021 as indicated by the chi-square statistical test with the result of a p-value of 0.318.